Performance of Silica Single Mode Hollow-core Optical Fibers in Optical Communications (Bulletin of Pure and Applied Sciences – Physics, 2022)
We have studied the performance of silica single mode hollow-core optical fibers in  optical communication. Silica single mode optical fibers form the core of high  capacity telecommunication network. Hollow-core optical fibers have an air filled  core surrounded with micro structured glass cladding allowing high level of light  confinement. Light guiding mechanism of Bragg, photonic band gap and  antiresonant fibers were considered. Nested antiresonant nodeless fibers and  conjoined fibers are the two most promising antiresonant fiber designs for achieving  ultra-low attenuation. Mode field adaptation using graded index multimode fiber; we have achieved record low insertions loss and also suppressed higher order  modes. Deposition of anti-reflective coating allowed reducing unwanted back  reflections. We have developed an approach for a hollow-core optical fiber of single  mode interconnection based on a modified fiber array technology which solved the  problem of back reflections by applying optical coating. Fundamental mode  coupling was achieved by using mode theory adapters in the form of graded index  multimode fibers.